United States’s Intervention against the Islamic State of Iraq and the Levant - Susilo, Indri; Putri, Rizqi Apriani; Azizah, Nur (Journal of Islamic World and Politics, 2018)
Combating terrorism is one of the foreign policy of the United States (US). The Islamic State of Iraq and The Levant (ISIL) or The Islamic State of Iraq and Syria (ISIS) is one of the movement deemed terrorists and has disturbed world peace. Ultimately the US decided to intervene to deal with the frequent acts of terror by ISIS which resulted in gross human rights violations. This article aims to find out how the US intervention to combat human rights abuses and acts of terror that have been done by ISIS. The research method which was used in this research is library research method, such as books, articles, journals, and various media which were relevant to this research. It has been found that the form of settlement efforts to reduce human rights violations, the US made preventive and repressive efforts. In preventive efforts, the US created an international coalition to gain support to counter terror committed by ISIS. Then the repressive effort is humanitarian intervention in the form of military aid and humanitarian aid. The US donates $ 1.2 billion annually and 350 million dollars as a form of military and humanitarian aid to combat ISIS.